Evaluation of dextrose prolotherapy versus extracorporeal shock wave therapy for pain relief and functional improvement in patients with knee osteoarthritis - I Made Yoga Prabawa; Noor Idha Handajani; Abdul Jabbar Al Hayyan; Lydia Arfianti; Atika (Physical Therapy Journal of Indonesia, 2026)
Background: Knee osteoarthritis (OA) remains a leading degenerative joint disease and a primary driver of chronic pain and disability among older adults. This condition is clinically defined by progressive cartilage degradation, joint stiffness, and a significant loss of functional mobility. Because standard conservative treatments often fail to provide adequate relief, there has been growing interest in regenerative approaches such as extracorporeal shock wave therapy (ESWT) and dextrose prolotherapy (DP). While their clinical use is increasing, direct comparative evidence regarding their relative effectiveness is still largely missing from some studies. This study aimed to evaluate the differences between ESWT and DP affect patients with knee OA in terms of functional improvement as measured by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and pain reduction as measured by the Visual Analogue Scale (VAS). Methods: This quasi-experimental study employed a pre-test–post-test randomised group design. Twenty patients with grade II–III knee OA who were not improving with traditional therapy were recruited and randomly assigned to two groups: ESWT (n=11) and DP (n=9). The interventions lasted for six weeks. Both before and after the intervention, the WOMAC and the VAS for pain were assessed as outcome measures. A statistical study was conducted to find differences both within and between groups. Results: Both the ESWT and DP groups had statistically significant improvements in all metrics, including pain (VAS), WOMAC pain, stiffness, disability, and total scores (p<0.05). However, there were no significant differences between the two groups for any of the evaluated outcomes (p>0.05). Conclusion: ESWT and DP were equally effective in reducing pain and improving functional outcomes in patients with knee OA. These findings indicate their role as a successful alternative therapy for people who don't receive enough relief from conventional medical therapies. Additional randomized controlled research are required to confirm these conclusions.